Targeting the Notch pathway: A potential therapeutic approach for desmoid tumors. Issue 22 (8th September 2015) - Shang, Hui; Braggio, Danielle; Lee, Ya‐Jung; Al Sannaa, Ghadah A.; Creighton, Chad J.; Bolshakov, Svetlana; Lazar, Alexander J. F.; Lev, Dina; Pollock, Raphael E.
Abstract : BACKGROUND: Desmoid tumors (DTs) are rare mesenchymal lesions that can recur repeatedly. When it is feasible, DTs are surgically resected; however, this often results in high recurrence rates. Recently, treatment with PF‐03084014, a potent γ‐secretase inhibitor, has been shown to have antitumor activity in several tumor types by affecting the WNT/β‐catenin pathway. Consequently, Notch pathway inhibition by PF‐03084014 might be a promising approach for DT treatment. METHODS: The expression of Notch pathway components was analyzed in DT tissues and cell strains with immunohistochemistry and Western blotting, respectively. A panel of DT cell strains was exposed to PF‐03084014 and evaluated for cell proliferation. Antitumor effects were assessed via cell cycle, apoptosis, and migration and invasion analysis. Cells treated with PF‐03084014 were characterized with a gene array analysis combined with Ingenuity Pathway Analysis. RESULTS: The results showed that Notch pathway components were expressed at different levels in DTs. Hes1 (Hes Family BHLH Transcription Factor 1) was overexpressed in DT tumors versus dermal scar tissue, and PF‐03084014 caused significant decreases in Notch intracellular domain and Hes1 expression in DT cell strains. PF‐03084014 decreased DT cell migration and invasion and also caused cell growth inhibition in DT cell strains, most likely through cell cycle arrest. Gene array analysis combined with Ingenuity Pathway Analysis showed that Wnt1‐inducible signaling pathway protein 2 possibly regulated Notch and WNT pathways after treatment with PF‐03084014 through integrin. CONCLUSION: Our findings suggest that the Notch pathway is an important DT therapeutic target. Furthermore, PF‐03084014 has significant antitumor activity against DTs, and it may be an alternative strategy for DT treatment. Cancer 2015;121:4088–4096. © 2015 American Cancer Society . Abstract : The Notch pathway is an important therapeutic target for desmoid tumors, and the γ‐secretase inhibitor PF‐03084014 has significant antitumor activity against desmoid tumors. The use of this inhibitor may be an alternative strategy for desmoid tumor treatment.